2014
DOI: 10.1128/cvi.00719-13
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Leptospiral Outer Membrane Lipoprotein LipL32 Reduces Kidney Invasion of Leptospira interrogans Serovar Canicola in Hamsters

Abstract: bThe Leptospira interrogans vaccines currently available are serovar specific and require regular booster immunizations to maintain protection of the host. In addition, a hamster challenge batch potency test is necessary to evaluate these vaccines prior to market release, requiring the use of a large number of animals, which is ethically and financially undesirable. Our previous work showed that the N terminus of the outer membrane protein LipL32 was altered in Leptospira interrogans serovar Canicola vaccines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Given the limitations of the whole-cell vaccines currently in use, identifying the perfect protein candidate has been a major effort in the field of vaccine development for leptospirosis 3 . Immunization with Lig proteins or LipL32 2,38,39 has been shown to confer protection, albeit not cross-protective immunity, against experimental infection. However, efficacy results have been proven difficult to replicate 2,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations of the whole-cell vaccines currently in use, identifying the perfect protein candidate has been a major effort in the field of vaccine development for leptospirosis 3 . Immunization with Lig proteins or LipL32 2,38,39 has been shown to confer protection, albeit not cross-protective immunity, against experimental infection. However, efficacy results have been proven difficult to replicate 2,40 .…”
Section: Discussionmentioning
confidence: 99%
“…In hamster model of leptospirosis, immunohistochemical analyses of L. kirschneri–infected kidneys have demonstrated the intense LipL32 expression in proximal tubule cells and the interstitium 16 . Vaccination with LipL32 reduces the severity of kidney inflammation in the hamsters infected with L. interrogans serovar Canicola in hamsters 36 . In this study, we demonstrated that the ectopic expression of LipL32 directly induced an inflammatory reaction and caused kidney injury, suggesting that LipL32 is a virulence factor and plays an important role in mediating the pathogenesis of renal injury in leptospirosis 37 .…”
Section: Discussionmentioning
confidence: 97%
“…The results of the experiment indicated that LipL32 may have a protective effect against the kidney invasion by the pathogen; histopathological analysis of kidneys indicated that the number of pathogens in the kidney was less in the immunized animals compared with the control. They also reported significant survival of the immunized group [34].…”
Section: Therapeutic Applicationsmentioning
confidence: 93%
“…The heat-labile endotoxin of E. coli further improved the immune response and protected the hamsters when challenged with the pathogenic strain. Humphryes et al [34] used LipL32 expressed in E. coli to immunize hamsters and challenged them with virulent Leptospira interrogans serovar Canicola strain Kito. The results of the experiment indicated that LipL32 may have a protective effect against the kidney invasion by the pathogen; histopathological analysis of kidneys indicated that the number of pathogens in the kidney was less in the immunized animals compared with the control.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%